The influence of social media marketing, brand image, and influencer endorsement towards purchase decisions of skintific skincare products on tiktok shop with trust as the mediator (study on generation Z consumers) - Levina, Widya; Malini, Helma; Pebrianti, Wenny; Hendri, M. Irfani; Jaya, Arman (Enrichment : Journal of Management, 2023)
Marketing through social media in recent years has been very widely used, ranging from skincare, fashion, and others, all the items we are looking for are very easy to find on social media with very broad access to e-commerce platforms. This study aims to determine the effect of social media marketing variables in selling skincare skintific products, then the brand image of skincare skintific products, and also the influence of Tasya Farasya's influencer endorsement in marketing these products through Tiktok with the Tiktok Shop feature, with the trust variable as an intervening variable. This study involved 263 people from various regions in Indonesia who were collected online using purposive sampling techniques through online questionnaires. The population of this study is Gen Z aged 17-25 years. The test tool to see the relationship between the independent variables and the dependent variable uses Structural Equation Modeling (SEM) with AMOS 24. The results of this study indicate that social media marketing, brand image, and influencer endorsement have a positive and significant effect on purchasing decisions. Trust has a positive and significant effect on purchasing decisions and significantly mediates social media marketing, brand image, and influencer endorsement on purchasing decisions.